A study on the relationship between college physical education teachers` job satisfaction, stress and burnout - Hao, H. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. II, 2008)
Introduction The main purpose of this study was to investigate the situation relating to how college PE teachers feel about job stress, burnout and satisfaction. Demographic variables affecting the teachers' job stress, job burnout and job satisfaction were also considered as well as the relationship between the three outcomes. Methods Data collection tools included a job stress inventory, and Maslach Burnout Inventory (MBI) job satisfaction inventory. Six hundred and ninety questionnaires were distributed and a total of 546 were returned with 405 of those deemed valid. Results / Conclusions The level of college PE teachers' job burnout is lower, job stress is higher, and the level of job satisfaction is also lower. Only a few demographical variables affect some factors significantly (e.g. length of service). Demographics mainly affect the level of job burnout, stress and satisfaction via two or three interactions. Male teachers' depersonalization are significantly higher than females and male teachers reported much lower personal accomplishments. Teachers who have worked between 10 to 15 years experienced the most serious burnout, stress and had the lowest job satisfaction. The linear regression indicates that when job stress increases, job burnout increases; however, when job stress increases, the job satisfaction decreases. Significant factors which affect the level of job burnout are work load physically, personal mental health and interpersonal relationships. Factors which affect the level of job satisfaction significantly are: management leadership, the hope of societies, work load, physical and mental health and interpersonal relationships. The structural equation model can explain the relationship between job stress, burnout and satisfaction.